A protocol for the management of hyponatremia peri‐liver transplant reduces post‐transplant neurological complications. Issue 5 (23rd March 2021) - Crismale, James F.; Huisman, Tsipora; Deshpande, Richa; Law, Cindy; Im, Gene Y.; Bronster, David; DeMaria, Samuel; Florman, Sander; Schiano, Thomas D.
Abstract: Rapid changes in serum sodium (ΔSNa) peri‐liver transplant (LT) predispose to post‐LT neurological complications (NC). We aimed to assess whether implementation of a protocol directed at limiting peri‐LT ΔSNa reduced post‐LT NC. A retrospective single‐center review of adult LT recipients from 1/2016 to 10/2017 was performed. Patients with hyponatremia (SNa < 135 mEq/L) within 7 days of LT were analyzed in two eras: pre‐protocol (1/2016‐9/2016) and post‐protocol (10/2016‐10/2017). The primary outcome was the development of NC within 1 month of LT. Perioperative ΔSNa (ΔSNaPost‐LT) was assessed as a secondary outcome. Among 85 and 107 patients who underwent LT pre‐ and post‐protocol, 39 (46%) and 42 (39%) were hyponatremic within 7 days of LT, respectively. Significantly fewer patients in the post‐protocol era developed NC vs. pre‐protocol (7.1% vs. 25.6%, p = .02). Additionally, fewer LT recipients in the post‐protocol era developed ΔSNaPost‐LT ≥ 10 mEq/L (9.5% vs. 30.7%, p = .02). Intraoperatively, more patients post‐protocol received hypotonic saline (33.3% vs. 2.6%, p < .01). Multivariable logistic regression revealed that transplantation in the post‐protocol era was associated with significantly reduced odds (odds ratio 0.11, 95% confidence interval 0.01–0.50) of developing NC. In conclusion, the implementation of a multidisciplinary protocol aimed at reducing ΔSNa peri‐LT was independently associated with a reduction in post‐LT NC.